Acetylene Welding of Brass Materials for Radiator Cover: A Study on the Weld Quality and Performance - Setyo, Nugroho; Harmi Tjahjanti, Prantasi Harmi Tjahjanti (Jurnal Improsci, 2023)
Brass material is important for all industrial parts. Brass had good ability work in cold or hot conditions, in solid state CuZn is capable of dissolving more crystals in the mixture. At temperatures of 902°C peritectic transformation occurred where Zn soluble in 32.5%. Solubility is increased up to a temperature of about 450 ° C to 39% and then in equilibrium will decrease, the length of the heating and cooling process is very long. With descriptive technique showed that the weld strength brass highest (7863.1 kgf / mm2) is that the surface of the specimen suffered welding rubbing with a gap distance of 0.2 and 0.3 mm, both with water cooling or air cooling, and the condition other relatively much lower strength (3144.89 kgf / mm2). Welding the workpiece surface is not polished strength is low. Specifically, properties - mechanical properties of brass can be improved by the addition of small amounts of other alloying elements without reducing the characteristics of the brass in general. But with a maximum limit zinc levels should not exceed 42% because it will result in a brass are fragile because of excess levels of zinc, and cannot be used commercially. with the addition of other elements as reinforcing elements of brass such as silicon, bismuth, selenium and others to improve the ability of the brass in the machining process. Welding results by using three different types of welding wire shows that, at the time of welding is performed with brass welding wire in the market there is no trouble found. Welding speed specimen is also calculated using a stopwatch, and the speed required for welding in 3 specimens, the average in the first specimen takes 5 minutes for the welding process. And the visual results produced is also satisfied.